Resource based view and resource dependence theory in decision making process of public organisation - research findings = Teoria zależności od zasobów oraz podejście zasobowe w procesie podejmowania decyzji w organizacji publicznej - wyniki badań empirycznych - Frąckiewicz-Wronka, Aldona; Szymaniec, Karolina (Zielona Góra: Faculty of Economics and Management Press)
One of the premises which build relationships between stakeholder and a public organisation are stakeholder's resources which public organisation would like to possess and use. The other one is configuration of resources possessed by the public organisation that should allow the unit in question to realize stakeholder's expectations. Above observations lead scientific inquiries to the two management theories - resource - based view (RBV) and resource dependence theory (RDT).
Keywords: podejście zasobowe; teoria zależności od zasobów; proces podejmowania decyzji; organizacja publiczna; szpital publiczny; resource based view (RBV); resource dependence theory (RDT); decision making process; public organisation; public hospital